Association of TGF-β1 with periodontitis patients in north Indian population - Ruchi Pandey; Sumit Bhateja; Lipika Gopal; Ankita Chhabrani; Anju Rana; Puneet Batra (Journal of Oral Biology and Craniofacial Research)
Introduction: Periodontitis is a complex disease caused by environmental and genetic factors. The course of periodontal destruction is influenced by local, ecological, and, predominantly, by genetic factors. Therefore, early detection of the disease through genomics and its course of destruction can be altered through genetic engineering, which can be a major breakthrough in the eradication of periodontitis. Aim: The purpose of this study is to find the genetic association of TGF-β1 gene polymorphisms in causing periodontitis in the North Indian population. Materials and methods: A total of 364 subjects were selected in the present study, and they were divided into two groups, viz. Healthy (Group A) and Periodontitis (Group B), with 182 subjects in each. The detailed case history was recorded, buccal swab samples were collected and stored in the sterile medium at 4 °C. Correlation studies on gene polymorphism with the disease occurrence were carried out by estimating allele frequency, Hardy-Weinberg equilibrium (HWE), and chi-square test (GenAlex package), and linkage disequilibrium and haplotype analysis (SHEsis). Result: The gene TGF-β1 showed a high rate of polymorphism in the north Indian population. The TGF-β1 gene showed polymorphism in the studied SNP sites. Among them, −29C/T and −788 C/T could differentiate the healthy and generalized periodontitis group; however, the localized periodontitis group could not be differentiated with any of the SNP loci. Conclusion: The gene TGF-β1 showed association with periodontitis in the North Indian Population.